Design of future mobility solutions for transportation - Rehman, Arsal (2018)
This report contains concept designs of a Folding Electric Bicycle as a future personal mobility transport solution. Moreover, the option of a having removable VTOL system for folding electric bicycles is explored and designed. First, studies on personal mobility device legislation in Singapore, ergonomics and anthropometry of cycling, basic flight theory, existing VTOL types, configurations and technologies are conducted. Then, conclusions from these studies are used as design inputs and specifications for the design portion of the report. After functional analysis of folding electric bicycle and the VTOL add-on, morphological charts were created to explore different design combinations. Concepts were made individually for folding electric bicycles and VTOL add-ons. These concepts were then combined to create overall concepts. Lastly, the most promising design was further developed through a preliminary CAD Model and its effectiveness was evaluated against the initial design specifications and inputs. The folding electric bicycle is designed as incremental improvement in current designs, while the VTOL option provides for an exploration of uncharted future mobility transport options.